1993
DOI: 10.1177/019251393014004005
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Middle-Range Theory of Father Involvement Postdivorce

Abstract: The problem addressed in the article is why so many fathers remove themselves from their children's lives after divorce. The authors develop a theory that offers a partial explanation of this phenomena based on the potential for change in the salience of a man's identity as a father postdivorce. Propositions are developed and hypotheses are derived from symbolic interaction and identity theory. The authors define and interrelate the concepts of identity, saliency, commitment, and significant others to explain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(79 citation statements)
references
References 32 publications
5
72
0
2
Order By: Relevance
“…An individual's identity is generally expected to express or manifest itself through behaviours which are coherent with this identity (Stryker & Serpe, 1994). In the parental domain, Ihinger-Tallman, Pasley, & Buehler (1993) have argued that father involvement is determined by the subjective importance attributed by fathers to their parental status and roles. However, empirical tests of this hypothesis have yielded mixed support.…”
Section: Paternal Identitymentioning
confidence: 99%
“…An individual's identity is generally expected to express or manifest itself through behaviours which are coherent with this identity (Stryker & Serpe, 1994). In the parental domain, Ihinger-Tallman, Pasley, & Buehler (1993) have argued that father involvement is determined by the subjective importance attributed by fathers to their parental status and roles. However, empirical tests of this hypothesis have yielded mixed support.…”
Section: Paternal Identitymentioning
confidence: 99%
“…Identity theory has been extended to address issues associated with men's paternal identity and involvement (Bruce & Fox, 1999;Futris & Pasley, 1997;Ihinger-Tallman, Pasley, & Buehler, 1995;Marsiglio, 1995b;1995c). This model emphasizes fathers' commitment to role identities that are negotiated within the context of structured role relationships.…”
Section: Fatherhood: Research Interventions and Policies 282mentioning
confidence: 99%
“…Union dissolution usually results in fathers physically moving away from their children making it difficult to maintain consistent contact (Amato & Gilbreth, 1998;Furstenberg, Morgan, & Allison, 1987). In addition, men experience a shift in their identities as fathers, particularly in relation to their roles and responsibilities toward their children, which makes it difficult to maintain a meaningful relationship with their nonresident children (Cherlin et al, 1991;Ihinger-Tallman, Pasley & Buehler, 1993). Research has shown that most unmarried and nonresident fathers do not maintain consistent contact with their children (Argys et al, 2007;Argys & Peters, 2001), though postdivorce fathers have been found to have higher levels of involvement than postcohabitation fathers (Laughlin, Farrie, & Fagan, 2009).…”
Section: Conceptual Backgroundmentioning
confidence: 99%